Genetic characterization of peste des petitis ruminants virus (PPRV) from Sulaimani/ Iraq by phylogenetic analysis and sequencing of nucleoprotein and fusion protein gene - Babashekh, 1 Muhamad omer; Rashid, Peshnyar Muhammad Atta; Marouf, Ari Salahadin; Raheem, Zhino Hussen; Amin, Kamaran Mohamad (Sulaimani Journal for Pure and Applied Sciences, 2014)
An outbreak of peste des petitis ruminants (PPR) in sheep was studied in Sulaimani/ Iraqi Kurdistan Region. The study provided the first molecular characterization of the PPRV lineage associated with fatal PPR infections in small ruminats. RT-PCR was used for diagnosis of PPRV outbreaks during 2012-2013 and the phylogenetic analysis results based on F and N genes. It was observed that three tested samples were positive for PPR, from which the two F genes (ppr/Kurdistan/2012, ppr2/Kurdistan/2012) were genetically close to the (KF478924 & JF274480) strain (turkey and Egypt) of lineage IV, respectively with 99% nucleotide sequence homogeneity. Regarding N gene, it was noticed that one sample (ppr3/Kurdistan/2013) where genetically close to (FJ795511, DQ840197 & DQ840190) strain (Emirate, Saudi Arabia & Israel) %99, %98 and %97 respectively. The current study suggested that there are at least two sources of PPRV in Iraq.
Keywords: PPRV Sulaimani peste des petits ruminants Kurdistan